Information Technology as a Catalyst for Innovation and Sustainability in the Creative Industry - Waqar Akbar Khan; Hind El Atmani (The Indonesian Institute of Science and Technology Research, 2025)
Creative industries and small and medium-sized enterprises (SMEs) play a vital role in economic growth, innovation, and cultural development, yet they face persistent challenges related to classification, financing, regulation, and market competition. Recent studies highlight that information technology (IT) has become a key enabler for enhancing creative capacity, operational efficiency, and competitiveness among creative SMEs. This paper examines the interconnected relationships between creative industry SMEs, IT usage, government policy, and innovation performance. Drawing on prior literature, it argues that IT adoption supports innovation, collaboration, customer engagement, and business sustainability. The adoption is through digital platforms, e-commerce, and creative technologies. However, effective IT utilization depends on supportive policy frameworks, access to skills, and adequate digital infrastructure. By synthesizing evidence on technological, institutional, and organizational factors, this study emphasizes the importance of integrated strategies that align IT development with government support to foster sustainable growth in creative industry SMEs.